2003
DOI: 10.1002/ejlt.200300866
|View full text |Cite
|
Sign up to set email alerts
|

Rapid simultaneous determination by proton NMR of unsaturation and composition of acyl groups in vegetable oils

Abstract: Abstract1H NMR spectra of 66 samples of edible oils from 14 different botanical origins were acquired. Assignment of signal spectra to the different types of hydrogen atoms was made and the areas of the signals determined. Considering that the area of the signals of the spectra is proportional to the number of hydrogen atoms of each type in the sample, it is possible to calculate not only the iodine value, but also the proportion of different acyl groups from the data. Determination of both parameters requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
195
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 205 publications
(225 citation statements)
references
References 17 publications
21
195
0
9
Order By: Relevance
“…The results are shown in Table 1. Oleic acid is an unsaturated fatty acid (ω9) and characteristic signals of its structure observed in the oils 1 H NMR spectra (Supplementary materials: Figures S1-S10) are in accordance with data described in the literature [15]. The contents of this acid, as estimated by the evaluation of corresponding signals in the NMR spectra of the oils analyzed, varied between 26.18% (Red Pupunha) to 75.38% (Tucumanzinho) in samples studied (Table 1).…”
Section: Resultssupporting
confidence: 86%
“…The results are shown in Table 1. Oleic acid is an unsaturated fatty acid (ω9) and characteristic signals of its structure observed in the oils 1 H NMR spectra (Supplementary materials: Figures S1-S10) are in accordance with data described in the literature [15]. The contents of this acid, as estimated by the evaluation of corresponding signals in the NMR spectra of the oils analyzed, varied between 26.18% (Red Pupunha) to 75.38% (Tucumanzinho) in samples studied (Table 1).…”
Section: Resultssupporting
confidence: 86%
“…The frequency of the narrow-bandwidth PRESS sequence was optimized separately for the 2.1, 2.3, or 2.8 ppm peak. (14,(29)(30)(31)(32). For the high purity linoleic acid, analysis was performed to compare the estimated amount of linoleic acid determined by each method.…”
Section: Resultsmentioning
confidence: 99%
“…The high spectral resolution is necessary to enable separate quantification of relevant lipid peaks such as the %2.1 ppm (allylic protons) and the %2.3 ppm (protons in a position to the carbonyl group) resonances. High-resolution NMR has been employed to identify the constituents of oils, animal fats, and extracts of rat adipose tissue (13)(14)(15)(16). Recently, in vivo MRS measurements of rodents (12,17,18) and humans (11) have been performed at high field strengths to calculate adipose tissue composition from the areas of the 2.1 ppm, 2.3 ppm, and 2.8 ppm (diallylic protons) proton lipid peaks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2. Method A [13] based on proportional methyl group in sample and method B [14] based on the methylenic hydrogen atom in α position. From Table II, it can be observed that 1 H NMR technique was analyzed and calculated the intensity for the unsaturated fatty acid compositions of RBO samples and GC-MS technique was provided all the saturated fatty acid compositions of the RBO samples.…”
Section: F Statistical Analysismentioning
confidence: 99%